2021
DOI: 10.1097/j.jcrs.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a new monofocal IOL with enhanced intermediate function in patients with cataract

Abstract: Purpose: To evaluate the effectiveness and safety of 2 enhanced monofocal intraocular lenses (IOLs). The TECNIS Eyhance IOL (Model ICB00) was compared with a standard monofocal IOL (TECNIS Monofocal, Model ZCB00). Setting: European multicenter study. Design: Prospective, bilateral, randomized, comparative/evaluator-masked, controlled study. Methods: Adult subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
144
11
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(178 citation statements)
references
References 18 publications
18
144
11
5
Order By: Relevance
“…In this refractive technology, continuous changes of power in the optic zone are created with higher-order asphericity. The higher-order aspheric monofocal IOLs are intended to provide improved intermediate vision [ 20 ]. They are visually indistinguishable from the same platform-standard monofocal lOLs.…”
Section: Discussionmentioning
confidence: 99%
“…In this refractive technology, continuous changes of power in the optic zone are created with higher-order asphericity. The higher-order aspheric monofocal IOLs are intended to provide improved intermediate vision [ 20 ]. They are visually indistinguishable from the same platform-standard monofocal lOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the Eyhance ICB00 IOL’s effectiveness as it provided improved intermediate vision compared to the monofocal 1-piece IOL [ 10 , 21 , 22 ]. In those previous studies, the Eyhance ICB00 IOL yielded better UIVA, higher spectacle independence at intermediate distance, and similar optical quality compared to the classic monofocal IOL, but provided similar distance and near visual acuities [ 10 , 21 , 22 ]. The results of this study also showed that the Eyhance ICB00 IOL produced better intermediate VA and similar optical quality compared to the ZCB00 IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this postoperative complaint is typically associated with multifocal IOLs rather than monofocal ones [15,16]. Recent clinical and laboratory studies demonstrated a comparable amount of dysphotopsia with the ICB00 and the control monofocal Tecnis IOL [2][3][4][5], which may be used as a reference to test the susceptibility of new mono-EDoF designs to produce such phenomena.…”
Section: Introductionmentioning
confidence: 99%